Reconstructing education management in the Indonesian army professionalism: RPL bridges academic gaps and faces digital age challenges - Wuryanto, Agus; Komariah, Aan; Yuniarsih, Tjutju; Suryana, Asep (Universitas Jambi, Indonesia, 2026)
This study examines strategies to enhance the academic qualifications and professionalism of the Indonesian National Armed Forces (TNI) through the implementation of Recognition of Prior Learning (RPL). In the realm of global military modernization, academic legitimacy has emerged as a critical complement to operational competence. This study employed a qualitative scoping review following the PRISMA framework. Data were collected from the Scopus database (2015–2025) using the Publish or Perish tool, yielding 200 articles; 15 met the inclusion criteria and were analyzed thematically. The findings reveal two key dimensions: (1) fundamental aspects, including civil–military integration, institutional alignment, and academic legitimacy; and (2) methodological aspects, such as the adoption of digital learning technologies, blended learning, and reflective-cognitive development. The study proposes four strategic directions: implementing RPL for credit recognition, aligning curricula with higher education standards, integrating digital technologies, and fostering a reflective academic culture. These strategies support transforming military education toward global competitiveness and professional excellence.